Auditors Reporting and its Role on Rationalizing economic decisions (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to release the concept of auditing reporting and its role in the rationalization of economic decisions in the companies listed in the Iraq Stock Exchange from the viewpoint of academics, professionals, investors and lenders. Auditor reporting witnessed the great progress in many areas addressed many of the previous studies compare with Iraqi auditors reporting because there are some defects in these aria .The research problem focused whether the auditor report in Iraq is contains useful information to rationalize investment decisions & lending decisions in the shareholding companies listed on the Iraq Stock Exchange , and under that premise , " There is statistically significant relationship between the reporting auditor in Iraq (within the report ) and the rationalization of investment and lending decisions in the companies listed on the Iraq Stock Exchange “.So the search based to view , analyze the results of the questionnaire prepared for this purpose and test the relationship between auditing reporting and decisions making rationality .The research found that, despite the usefulness of the information contained in the auditor 's report issued by companies listed on the Iraq Stock Exchange for the purpose of rationalizing investment and lending decisions ,it requires the development of the auditor 's report and improve the content of its information, as it confirms investors and lenders as well as academics and professionals in this context the need to develop auditor reporting and improve the content of his report information to have an active role in the rationalization of economic decisions.